Pelaksanaan Tingkatan-Tingkatan Hak Tanggungan Dalam Perjanjian Kredit Dengan Jaminan Hak Atas Tanah - Ratnasari, Agustina Dewi; , Septarina Budiwati, S.H., M.H (2017)
This research aims to know the process she was a dependent right levels that exist in the Office of the notary and land deed official Seno Budi Santoso, S.H and constraints in the implementation of the right level of dependents. The method of the approach used in this research is empirical and juridical nature of the descriptive. The location of the research done in the notary office and the land deed official Seno Budi Santoso, S.H law based in Sukoharjo. The data collection method used is by the techniques of field studies through interviews and a literature study also be data from library materials. Based on the results of the research and the discussion then it can be inferred that the implementation level of rights dependent on the Office of the notary and land deed official Seno Budi Santoso, S.H occurs due to the imposition of the rights guarantee of taking action against property rights Dependent Upon the same Ground more than once with the same lender based on Additional Credit Agreement proposed by the debtor to the Creditor's rights Holder Agreements i. Imposition committed as many as 6 (six) times. But not all guarantee land rights can be a dependent rights will be loaded, only large-scale credit application only in the register of load dependent rights, the two factors i.e. administrative fee registration rights agreements are expensive and the process of the imposition of a right old dependents.